An Optical System with Brightness Amplification for Studying the Surface of Metal Nanopowders during Combustion; Instruments and Experimental Techniques; Vol. 63, iss. 3 - Gubarev F. A. Fedor Aleksandrovich; Kim S.; Li Lin; Mostovshchikov A. V. Andrey Vladimirovich; Ilyin A. P. Aleksandr Petrovich (2020, 2020)
Title screen